Dynamic response analysis of shrouded blades under impact-friction considering the influence of passive blade vibration. (7th July 2021) - Guo, Xumin; Ni, Kaixuan; Ma, Hui; Zeng, Jin; Wang, Zelong; Wen, Bangchun
Highlights: The established shrouded blade model can take into account elastic support, shroud position change, stagger angle, and twist angle. The dynamic model derived in this paper considers the coupling effect of impact and friction of adjacent shrouds and the inertia effects of passive blades. The geometric structure of the shroud is considered by deducing a new mode shape function, and the construction of an elastic support beam with a variable section is realized. Abstract: A new dynamic model of shrouded blades with elastic support and variable cross-section is derived based on the Timoshenko beam theory, in which factors to be considered include centrifugal stiffening, spin softening, Coriolis force, blade stagger angle, and twist angle. The proposed model (PM) is verified by comparing the dynamic frequency results of the finite element model (FEM) and the PM. An impact-friction model of shrouded blades is established which can take into account the inertia effects of two passive blades. By comparing the vibration response of the two models (PM and FEM), the established impact-friction model is verified. Finally, the influences of normal contact stiffness, blade root support stiffness, and shroud position on the vibration response of the system are analyzed. Meanwhile, bifurcation diagrams, time-domain waveforms, phase diagrams, Poincaré maps, and frequency spectrum are utilized to analyze the nonlinear vibration characteristics of shrouded blades. The results show that the impact and friction between adjacent shrouds will cause the complex nonlinear vibration of the blades. Under small initial gaps, hard nonlinear phenomena can be observed in the vibration response of the shrouded blade. While under small initial preloads, it shows an obvious soft nonlinear phenomenon. Furthermore, with the increase of normal contact stiffness and blade root support stiffness, the resonance peak of the blade-tip flexural displacement decreases. When the shroud is closer to the blade-tip of the blade, the vibration reduction effect of the shrouded blade is better. The active blade experiences the chaos, period-one motion due to the nonlinear behavior of the impact-friction coupling at the adjacent shroud contact interfaces.